CONFLICTS՚ SOURCES AND STRESSFUL FACTORS IN MODERN ORGANIZATIONS - I. A. Romanova; N. I. Laas; E. V. Gurova (Вестник университета)
The article gives the results of a study of managers and ordinary employees of Russian organizations on the problem of identifying sources of conflicts and stress factors affecting the functioning of companies. The paper analyses in detail and presents the answers of respondents to the questionnaire about the frequency of the confrontation; on the impact of collisions on staff productivity and on the development of unfavorable mental states of workers; on the role of management and ordinary employees in the emergence of conflicts; about the main reasons for the conflict confrontation; on the system of conflict and stress management, including measures to prevent and resolve them. The results of the survey showed that both the company’s management and ordinary personnel are involved in conflicts, and the leading source of confrontation, according to the majority of respondents, is the individual psychological characteristics of employees. At the same time, the conflicts themselves act as stress factors, having a direct adverse effect on the efficiency of activities and causing specific unwanted emotional reactions. Among other things, the results of the survey showed that the organizations where the respondents work do not have a well-functioning system of conflict management. The research results are practice-oriented.